The Policy Formulation of Multi Stakeholder Consultation Forum for Development Planning - Anwar Sadat; Hastuti (International Journal of Advanced Science and Technology, 2020)
This current study aims to describe and to investigate the policy formulation of a multi-stakeholder consultation forum for developing (Musrenbang) in Baubau, moreover, to identify the supporting and inhibiting factors of the policy formulation of multi-stakeholder consultation forum for developing (Musrenbang) in Baubau. To achieve the intended goals, this article uses a qualitative approach to literature studies on some documents and data sources, which address the framework of the Baubau City Development Planning Policy in the phases following the introduction of the Musrenbang process. Such papers, either in study reports or data from different government agencies, as well as news from certain mass media. The data are then qualitatively evaluated using the theoretical framework available for Musrenbang and group involvement. The results of this research suggested that the policy process for the establishment of a multi-stakeholder consultation forum was underway. the mechanism of the implementation was mandated by law, the priority program as a reference in proposing each program discussed in the musrenbang agenda from the level villages, districts, and cities. The supporting and inhibiting factor in the process of the musrenbang policy formulation was the number of proposed programs executed but the realization from local government was poor, so the community’s perceptions decline in pretending the musrenbang as a forum that could realize what the community objectively needs in real terms.